2009
DOI: 10.1016/j.nut.2008.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Dairy protein and leucine alter GLP-1 release and mRNA of genes involved in intestinal lipid metabolism in vitro

Abstract: Objective-A growing body of evidence supports an antiobesity effect of dairy products; however, the mechanisms remain unclear. The objective of this study was to explore possible intestinal mechanisms by which dairy delivers an antiobesity effect. The human intestinal cell line, NCI-H716, was used to test the hypothesis that branched-chain amino acids and dairy proteins regulate satiety hormone secretion and modulate genes involved in fatty acid and cholesterol metabolism.Methods-In dose-response (0.5%, 1.0%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
3
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 49 publications
5
99
3
5
Order By: Relevance
“…We showed significantly greater GLP-1 and GIP responses in the ORAL BCAA test, and there was no significant incremental change observed in the IV and PLACEBO test. We showed both GLP-1 and GIP responses after oral BCAA, which is in contrast to previously published data [13,16]. Whether this is due to a higher dose used in the current study or a special incretin-stimulating effect of BCAA remains to be established.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We showed significantly greater GLP-1 and GIP responses in the ORAL BCAA test, and there was no significant incremental change observed in the IV and PLACEBO test. We showed both GLP-1 and GIP responses after oral BCAA, which is in contrast to previously published data [13,16]. Whether this is due to a higher dose used in the current study or a special incretin-stimulating effect of BCAA remains to be established.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that intra-duodenal [12] as well as oral administration [13] of an AA mixture elicit a greater insulin response compared with IV administration. Increase in incretin levels has already been shown after oral whey administration and AA mixtures [3,13,14,15] and in vitro GLP-1 response has been demonstrated in an intestinal cell line after incubation with BCAA [16]. It could be therefore hypothesized that incretin effect of oral BCAA contributes significantly to insulinotropic properties of whey and AA mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Peynir altı suyu proteinleri, yeni protein sentezinde önem taşıyan zincir aminoasitlerin %26'sına kadar sağlamakta-dır. 10,20 …”
Section: Egzersi̇zunclassified
“…8,9 Lözin, m-RNA fonksiyonunu kontrol eden proteinlerin dönüşümlü fosforilizasyonunu kolaylaştırmakta ve böylece kas protein sentezini artırmaktadır. 10 İskemik atak geçiren yaşlı hastalarda peynir altı suyu proteini ihtiva eden enteral formülasyonların inflamasyonu azalttığı ve antioksidan savunmayı artırdığı rapor edilmiştir.…”
unclassified
“…A number of other dietary-based GLP-1 secretagogues have been reported [4,13,17,22,26] but pharmacologically there is a focus on targeting several intestinal GPCRs believed to be important in modulating gut hormone secretion. These include the bile acid receptor TGR5 [25] and fat-sensing receptors GPR40, GPR119, and GPR120 [38] all of which are present on the surface of enteroendocrine cells.…”
Section: Introductionmentioning
confidence: 99%